Shadow - Swallow, James (Forge, a Tom Doherty Associates Book, 2022)
"Ex-MI6 officer Marc Dane and his partner, Lucy Keyes, are bound together in a desperate search for the sinister organization plotting the release of a deadly virus on the world. In their frantic race against time, Dane and Keyes will be tested more than ever before as they seem to find themselves one step behind at every turn. It will take everything they have to expose the evil forces lurking in the shadows and put a stop to this unstoppable pathogen... and even everything might not be enough"